RELATIONS OF BRAZIL WITH SOUTH AFRICA AND ANGOLA: EFFORTS FOR THE MAINTENANCE OF SECURITY IN SOUTH ATLANTIC - Goldoni, Luiz Rogério Franco; Ciribelli, Sandro de Nazareth (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
With a view towards the defense of their vital spaces (South Atlantic) and seeking greater international prominence, Brazil has intensified its relations with the African continent. Thus, the present study aims to analyze the bilateral relations between Brazil and both South Africa and Angola, highlighting these relationships effects on the maintenance of security in the South Atlantic. It is studied the growing interconnection between the foreign policy and the Brazilian defense policy, the military cooperation agreements and joint naval exercises.